Long-term cattle manure addition enhances soil-available phosphorus fractions in subtropical open-field rotated vegetable systems - Mao, Yanting; Hu, Wei; Li, Yongmei; Li, Yuan; Lei, Baokun; Zheng, Yi (Frontiers in Plant Science, 2023)
Introduction Evaluation of the changes in phosphorus (P) fractions (various P forms) and their availability at different soil layers is critical for enhancing P resource use efficiency, mitigating subsequent environmental pollution, and establishing a suitable manure application strategy. However, changes in P fractions at different soil layers in response to cattle manure (M), as well as a combined cattle manure and chemical fertilizer application (M+F), remain unclear in open-field vegetable systems. If the amount of annual P input remains the same, identifying which treatment would cause a higher phosphate fertilizer use efficiency (PUE) and vegetable yield while simultaneously reducing the P surplus is especially warranted. Methods Based on a long-term manure experiment that started in 2008, we used a modified P fractionation scheme to analyze P fractions at two soil layers for three treatments (M, M+F, and control without fertilizer application) in an open-field cabbage (Brassica oleracea) and lettuce (Lactuca sativa) system, and assessed the PUE and accumulated P surplus. Results The concentrations of the soil P fractions were higher in the 0–20-cm soil layer compared to the 20–40-cm layer, except for organic P (Po) and residual-P. M application significantly increased the inorganic P (Pi) (by 8.92%–72.26%) and the Po content (by 5.01%–61.23%) at the two soil layers. Compared with the control and M+F treatments, M significantly increased residual-P, Resin-P, and NaHCO3-Pi at both soil layers (by 31.9%–32.95%, 68.40%–72.60%, and 48.22%–61.04%), whereas NaOH-Pi and HCl-Pi at 0–20 cm were positively correlated with available P. Soil moderately labile-P was the predominant P component in the two soil layers (accounting for 59%–70%). With the same annual P input amount, M+CF created the highest vegetable yield (117.86 t ha-1), and PUE (37.88%) and M created the highest accumulated P surplus (128.80 kg ha-1yr-1). Discussion Collectively, a combined manure-chemical fertilizer application has great potential to yield a long-term positive outcome both in terms of vegetable productivity and environmental health in open-field vegetable systems. This highlights the methods’ benefits as a sustainable practice in subtropical vegetable systems. Specific attention should be given to a P balance to avoid excessive P input if a rational strategy for manure application is to be attained. This is especially the case for stem vegetables that require manure application and decreases the environmental risk of P loss in vegetable systems.